2012
DOI: 10.1021/nn302891u
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Cell Detachment, Patterning, and Regrowth on Gold Nanoparticle Functionalized Surfaces

Abstract: We report on the selective cell detachment from nanoengineered gold nanoparticle (AuNP) surfaces triggered by laser irradiation, which occurs in a nonthermal manner. The gold nanoparticle-based surfaces reveal good adhesion of NIH3T3 fibroblast cells. Patterning is achieved by lithographic microcontact printing, selective gold nanoparticle deposition, and by laser beam profiling. It is shown that the effectiveness of fibroblast cell detachment depends on the cell age, laser power, and AuNP patterning profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 91 publications
0
51
0
Order By: Relevance
“…ROS damages cell membranes and that led to cell detachments. Furthermore, surface recovery due to migration of cells from non‐irradiated areas was observed …”
Section: Self‐assembled Monolayers Of Nanomaterials As Biomaterialsmentioning
confidence: 98%
“…ROS damages cell membranes and that led to cell detachments. Furthermore, surface recovery due to migration of cells from non‐irradiated areas was observed …”
Section: Self‐assembled Monolayers Of Nanomaterials As Biomaterialsmentioning
confidence: 98%
“…Although the need for less-invasive cell harvesting methods has been noted in the literature, only a few works, which either require electricity-induction (Yeo et al, 2001, Inaba et al, 2009, Wildt et al, 2010, Zhu et al, 2008), pH change-induction (Chen et al, 2012, Guillaume-Gentil et al, 2011), or light-induction methods (Hong et al, 2013, Pasparakis et al, 2011, Sada et al, 2011, Shin et al, 2011, Kolesnikova et al, 2012, Higuchi et al, 2004) have successfully addressed this issue. Only a few non-invasive cell detachment methods such as those that use aptamers (Wan et al, 2012, Zhang et al, 2012b, Zhu et al, 2012) or hydrogels (Plouffe et al, 2009a, Hatch et al, 2011, Hatch et al, 2012) have been shown to be successful for cell detachment.…”
Section: 0 Challenges and Opportunities For Further Research And Comentioning
confidence: 99%
“…43 Fibroblasts were cultured on gold nanoparticle based surfaces. Gold nanoparticles have strong photoabsorpotion in the green spectral range.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%